2020
DOI: 10.1002/ajpa.23994
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measurements of the talus and calcaneus in the adult pes planus foot type

Abstract: Objective A distinctive feature of the modern human foot is the presence of a medial longitudinal arch when weight‐bearing. Although the talus and calcaneus play a major role in the structure and function of the human foot, the association between the morphology of these bones and longitudinal arch height has not been fully investigated. A better understanding of this relationship may assist in the interpretation of pedal remains of fossil hominins, where features of the foot and ankle morphology have been des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 65 publications
1
14
1
Order By: Relevance
“…In an additional analysis conducted in the present study, we similarly obtained a positive correlation of the ratio of the height to the length of the calcaneus with the foot arch height when non-weight-bearing (r = 0.294, P = 0.028). By contrast, in a study by Agoada and Kramer 30 , all variables, including the ratio of the height to the length, related to the height of the talus did not correlate with the foot arch height. Furthermore, the result of additional analysis in the present study showed a negative correlation of the ratio of the height to the length of the talus with the foot arch height (r = − 0.448, P = 0.001), suggesting that a taller talus may be a negative morphological factor for modeling a higher foot arch height.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In an additional analysis conducted in the present study, we similarly obtained a positive correlation of the ratio of the height to the length of the calcaneus with the foot arch height when non-weight-bearing (r = 0.294, P = 0.028). By contrast, in a study by Agoada and Kramer 30 , all variables, including the ratio of the height to the length, related to the height of the talus did not correlate with the foot arch height. Furthermore, the result of additional analysis in the present study showed a negative correlation of the ratio of the height to the length of the talus with the foot arch height (r = − 0.448, P = 0.001), suggesting that a taller talus may be a negative morphological factor for modeling a higher foot arch height.…”
Section: Discussioncontrasting
confidence: 57%
“…The calcaneus and talus are known to be pivotal bones for foot arch formation 30 , 31 . The results of this study showed that although there were no correlations of absolute and relative heights of the talus with the foot arch height and its index, absolute and relative heights of the calcaneus correlated positively with the foot arch height and its index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The navicular index values of these 2 ft were 7.32 and 6.76, and the scores in the simple footprint assessment board were 0.5 and 1, respectively. On the other hand, it has been reported that if calcaneal inclination angle is less than 18 degrees, flat feet are more likely [33]. These results for known cases of flatfoot suggest that the diagnosis of flatfoot is highly likely if the cord of the simple footprint assessment board either passes through the great toe or over its medial side.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, the validity of this board for the diagnosis of flexible flatfoot, which is loss of the inner arch in a loaded condition and more common in children, could not be examined because non weight-bearing CT images were applied to measure the navicular index. However, the results of the tibiocalcaneal angle and calcaneal inclination angle were well-correlated with both weight-bearing and nonweight-bearing conditions [21,33]. Future research should be conducted with weight-bearing CT images for radiological evaluation to clarify the usefulness of simple tools like the simple footprint assessment board for diagnosis of flexible flatfoot.…”
Section: Discussionmentioning
confidence: 96%